2020
DOI: 10.7717/peerj.10260
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the dynamics of individual gut microbiome of sea cucumber Apostichopus japonicus during gut regeneration

Abstract: Sea cucumbers possess the remarkable capacity to regenerate their body parts or organs. Regeneration of host organs and/or body parts involves reconstruction of the host associated microbiota, however, the dynamics and contribution of microbiota to the regeneration process are largely unknown due to a lack of experimental models. To track the dynamics of individual gut microbiomes during gut regeneration, both caged mariculture and laboratory isolator systems of sea cucumbers (Apostichopus japonicus) were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Moreover, the microbial community composition in the sea cucumber gut at 42-56 dpe was notably different from that at the initial stage, suggesting the formation of a novel microbiota during gut regeneration. Moreover, this result is consistent with previous findings in the sea cucumber Sclerodactyla briareus and A. japonicus (Weigel, 2020;Yamazaki et al, 2020). Similarly, the source tracking results suggest that the A. japonicus gut bacterial community is reconstructed from the bacterial community present in the residual esophagus and stomach after evisceration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the microbial community composition in the sea cucumber gut at 42-56 dpe was notably different from that at the initial stage, suggesting the formation of a novel microbiota during gut regeneration. Moreover, this result is consistent with previous findings in the sea cucumber Sclerodactyla briareus and A. japonicus (Weigel, 2020;Yamazaki et al, 2020). Similarly, the source tracking results suggest that the A. japonicus gut bacterial community is reconstructed from the bacterial community present in the residual esophagus and stomach after evisceration.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this result is consistent with previous findings in the sea cucumber Sclerodactyla briareus and A . japonicus (Weigel, 2020 ; Yamazaki et al, 2020 ). Similarly, the source tracking results suggest that the A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tnr plays an important role in the development of the nervous system, the regeneration of tissues and organs after trauma and it can regulate the morphology of extracellular matrix (Meloty-Kapella et al, 2006). Another study showed that tnr could act as an important ECM component involved in neurodevelopmental regeneration and participates in the intestinal regeneration of A. japonicus (Yamazaki et al, 2020). We speculated that A. japonicus could repair tissue damage during heat stress and resist environmental changes by up-regulating the expression of tnr.…”
Section: Discussionmentioning
confidence: 95%
“…After the recent findings of potential physiological roles in gut microbiomes of the sea cucumber A. japonicus (Yamazaki et al, 2016), dynamics of the microbiome, in particular How sea cucumbers shape their microbiomes? has been a central question (Yamazaki et al, 2020). Among a series of studies on the sea cucumber microbiome, first colonizers on the animal guts called Pioneer Microbes are worth studying in sea cucumbers as they potentially contribute to improving aquaculture technology and accumulate biological knowledge on gut microbiome evolution compared to those in humans (Wopereis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%